Effect of dietary supplementation of Ligustrum lucidum on performance, egg quality and blood biochemical parameters of Hy-Line Brown hens during the late laying period. (16th March 2017) - Li, X. L.; He, W. L.; Yang, M. L.; Yan, Y. M.; Xue, Y. H.; Zhao, S. T.
Abstract : The fruit of Ligustrum lucidum (FLL, Nuzhenzi in Chinese) is an important traditional medicine, and have attracted significant research attention because of their various biological activities. However, there are few research reports available on the use of FLL as a feed additive in livestock nutrition, particularly in layers. This study was conducted to determine the effects of supplementation of the diet of laying hens with FLL on laying performance, egg quality and blood metabolites. A total of 360 72-week-old hens were allocated to three dietary treatments (eight replications of 15 hens/treatment group) and were fed either a control diet or a diet supplemented with an inclusion level of 0.25% or 0.50% of FLL powder in the final feed, until 78 weeks of age. Hens were housed in a three-tier cage system. Feed and water were provided ad libitum . Blood samples and eggs were collected at the end of the experiment. The results showed that dietary supplementation with FLL did not affect egg weight, feed conversion ratio, eggshell thickness, albumen height, egg yolk color, eggshell breaking strength or egg shape index. However, FLL supplementation significantly decreased ( P <0.001) mortality, cracked-egg rate and blood serum levels of cholesterol, low-density lipoprotein cholesterol, triglycerides and alanine aminotransferase, and increased ( P <0.001) blood serum levels of high-density lipoprotein cholesterol. No differences in serum levels of total protein, albumin, glucose, calcium, aspartate aminotransferase or alkaline phosphatase were observed in hens fed FLL compared with the control group. It can be concluded that FLL, at a supplementation level of 0.25% final feed, can be used as an effective feed additive to improve the performance of laying hens during the late laying period.